Academic Dashboard For Monitoring KPI Based Using Data Feeder Dikti - Andi Leo; Ardiane Rossi Kurniawan Maranto; Fernando Fanjaya; Jupiter Supriyadi (bit-Tech, 2022)
University management requires accurate and fast academic reports that make it easier to make strategic decisions and in order to improve the quality of education. Therefore we need a tool that can monitor, evaluate and measure the performance of universities. A common problem is that there is a lot of academic data stored but to present it in reports at the time of evaluating academic activities is difficult and takes a long time. Academic evaluation can be presented with a dashboard so that it becomes easy for decision making. Dashboard is a page that shows graphs as KPIs (Key Performance Indicators) of an organization and provides all the important measurements needed to make key executive decision making. Universities in Indonesia report data on students, lecturers and lecture activities to the PDDIKTI (Higher Education Database). The data contained in the PDDIKTI Feeder is made an academic Dashboard in the form of visualization to assist and support decision making at the academic level and also to monitor using KPI as an evaluation. With the existence of an academic dashboard based on KPI, the presentation of reports becomes faster and easier to understand because it is in the form of visuals and indicators to find out what things need to be improved and the extent to which the achievements of each academic component are used as benchmarks in submitting study program accreditation.